Pseudochromine and pseudoplesiopine dottyback fishes from the Socotra Archipelago, Indian Ocean, with descriptions of two new species of Pseudochromis Rüppell (Perciformes: Pseudochromidae) - Gill, Anthony C.; Zajonz, Uwe (Zootaxa, 2011)
Species of pseudoplesiopine and pseudochromine fishes from the Socotra Archipelago are reported based mainly on collections made in 1999 and 2000. Two species of the pseudoplesiopine genus Chlidichthys Smith are recorded: C. bibulus (Smith) and C. cacatuoides Gill and Edwards. Seven species of the pseudochromine genus Pseudochromis Rüppell are recorded: P. chrysospilus sp. nov., P. leucorhynchus Lubbock, P. linda Randall and Stanaland, P. nigrovittatus Boulenger, P. sankeyi Lubbock, P. socotraensis sp. nov. and an undetermined species (allied to P. punctatus Kotthaus). Pseudochromis chrysospilus belongs to a newly diagnosed P. caudalis-complex; it differs from other members of the complex in various meristic and coloration details. Pseudochromis socotraensis belongs to a newly diagnosed P. dutoiti-complex; it differs from other members of the complex in adult size, various meristic characters and live coloration. Based on both the collection records and additional visual records made in 1999 and 2000 the archipelagic distribution ranges of each species and the biotopes inhabited by them are described. Two additional species are tentatively reported from the Socotra Archipelago on the basis of sight records: P. dixurus Lubbock and P. omanensis Gill and Mee.